Does causal reasoning lead to moral reasoning? Consumers' responses to scandalized athletes and endorsements. Issue 3 (24th August 2021) - Kim, Daehwan; Lee, Joon Sung; Jang, Wonseok (Eric); Ko, Yong Jae
Abstract : Purpose: Marketers and brand managers are subject to reputational crises when their endorsers are involved in scandals. To effectively manage such crises, it is imperative to understand (1) the underlying mechanisms through which consumers process negative information surrounding morally tainted endorsers, and (2) how these mechanisms affect consumer behavior in the context of athlete scandals. Design/methodology/approach: Drawing on attribution theory and the moral reasoning strategy framework, we investigate the impact of attribution on moral reasoning strategies, and the impact of such strategies on consumers' responses to scandalized athletes and endorsements. Findings: Overall, our results demonstrate that the same scandal can be evaluated differently, depending on its information, including the consensus, distinctiveness, and consistency of the scandal. The results of Study 1 show that in the context of an on-field scandal, individuals engage in a sequential cognitive process in which they go through attribution, the choice of a moral reasoning strategy, and ultimately a response. The results of Study 2 reveal that in the context of an off-field scandal, attribution directly influences consumers' responses. Originality/value: We extend the existing literature on the moral reasoning of athlete scandals by suggesting that attribution is a determinant of moral reasoning choice in the context of on-field scandals. We also extend the sports marketing and consumer behavior literature by suggesting that consumers' diverse reactions to athlete scandals depend on their attribution patterns and moral reasoning choices.